Sutureless vs. rapid-deployment valve: a systemic review and meta-analysis for a direct comparison of intraoperative performance and clinical outcomes - Wang, Chenhao; Xie, Yi; Zhang, Hongwei; Yang, Peng; Zhang, Yu; Lu, Chen; Liu, Yu; Wang, Haiyue; Xu, Zhenyuan; Hu, Jia (Frontiers in Cardiovascular Medicine, 2023)
Background Sutureless and rapid-deployment valves are bioprostheses anchoring within the aortic annulus with few sutures applying for aortic valve replacement. Considering the 3F Enable valve been off-market, the only two sutureless and rapid-deployment valves available on the world marketplace at this time are the Perceval and Intuity valves. However, direct comparison of the performances of these two valves still remains inadequate. Purpose We performed this systematic review and meta-analysis compare the intraoperative performance and clinical outcomes between the Perceval valve and the Intuity valve under sutureless and rapid-deployment aortic valve replacement. Methods We systematically searched electronic databases through PubMed/MEDLINE, OvidWeb, Web of Science, and Cochrane Central Register of Controlled Trials for studies comparing sutureless valve (the Perceval) and rapid-deployment valve (the Intuity) under aortic valve replacement. Our primary outcomes were early mortality and post-operative transvalvular pressure gradients; the secondary outcomes were defined to include aortic cross-clamp and cardiopulmonary bypass time, paravalvular leak after aortic valve replacement, need of pacemaker implantation, postoperative neurological events and intensive care unit stay. Results The present meta-analysis included ten non-randomized trials with 3526 patients enrolled (Sutureless group = 1772 and Rapid-deployment group = 1754). Quality assessments were performed as the mean scores of the studies were 6.90 (SD = 0.99) out of 9 according to the Newcastle-Ottawa Scale. Compared with rapid-deployment aortic valve replacement, sutureless aortic valve replacement was associated higher mean and peak transvalvular pressure gradients postoperatively. While aortic cross-clamp and cardiopulmonary time were less needed in sutureless aortic valve replacement versus rapid-deployment aortic valve replacement. There was no evidence of significant publication bias observed by the funnel plot and Egger’s test. Conclusions For postoperative hemodynamics, sutureless aortic valve replacement was associated with increased mean and peak transvalvular pressure gradients compared to rapid-deployment aortic valve replacement. In sharp contrast, sutureless aortic valve replacement significantly reduced the amount of time needed for the aortic cross-clamp and the cardiopulmonary bypass. Prospero number CRD42022343884.